Dairy Consumption and Risk of Testicular Cancer: A Systematic Review. (4th July 2018) - Signal, Virginia; Huang, Stephanie; Sarfati, Diana; Stanley, James; McGlynn, Katherine A.; Gurney, Jason K.
ABSTRACT: Dairy consumption has been studied extensively in terms of its relationship with testicular cancer (TC), yet this relationship remains unclear. In this systematic review, we aimed to answer whether TC development is associated with (a) high amounts of dairy product consumption, (b) the type of dairy product consumed, (c) increasing levels of dairy product consumption, and (d) dairy consumption during certain periods during the lifecourse. Following a systematic review of the literature, eight studies (all case-control studies) were included in our review. The included studies varied in terms of the dairy product(s) investigated (milk, cheese, cream, butter, and yoghurt) as well as the type of exposure to dairy consumption (e.g., high vs. low exposure, dose-response, and timing during lifecourse). We found that there was no strong evidence that high levels of dairy consumption are associated with risk of TC, conflicting evidence of a dose–response relationship, inconsistent evidence on whether certain types of dairy are more strongly associated with TC than others, and conflicting evidence that exposure during certain life-course periods affects TC risk more than other periods. There is no consistent evidence to support the premise that dairy product consumption is associated with the risk of TC development.